Ventajas y desventajas de la inmunocastración en sistemas porcícolas - Amado Vivas, Luz Ángela; Ferrao Zabala, Heral Mateo; Flórez Quiroga, Liceth Johana (Universidad Antonio Nariño, 2023)
Surgical castration has been the oldest method that producers have used, however, it brings many effects that harm the animal and that will be reflected in production losses.